Cytokine Receptor Profiling in Human Colonic Subepithelial Myofibroblasts: A Differential Effect of Th Polarization–Associated Cytokines in Intestinal Fibrosis. Issue 10 (1st June 2018) - Filidou, Eirini; Valatas, Vasilis; Drygiannakis, Ioannis; Arvanitidis, Konstantinos; Vradelis, Stergios; Kouklakis, Georgios; Kolios, George; Bamias, Giorgos
Abstract: Background: Colonic subepithelial myofibroblasts (cSEMFs) are mesenchymal cells with a pivotal role in the pathophysiology of Crohn's disease (CD) fibrosis. Here, we demonstrate for the first time a complete expression mapping of cytokine receptors, implicated in inflammatory bowel diseases, in primary human cSEMFs and how pro-inflammatory cytokines regulate this expression. Furthermore, we show the effect of Th1-, Th2-, Th17- and Treg-related cytokines on a fibrosis-related phenotype of cSEMFs. Methods: Colonic subepithelial myofibroblasts were isolated from healthy individuals' colonic biopsies. Interleukin (IL)-1α- and/or tumor necrosis factor (TNF)–α–induced mRNA and protein expression of cytokine receptors was assayed by quantitative reverse transcription polymerase chain reaction (qRT-PCR) and immunofluorescence, respectively. Th-related cytokine effects on mRNA and protein profibrotic factor expression were analyzed by qRT-PCR and/or colorimetric assays and on the wound-healing capacity of cSEMFs by scratch test. Results: In cSEMFs, we observed basal cytokine receptor expression, which was modified by IL-1α and TNF-α. Th1-related cytokines upregulated tissue factor (TF), collagen, fibronectin and matrix metalloproteinase (MMP)–1 and downregulated α–smooth muscle actin (α-SMA), MMP-9, and wound healing rate. Th2-related cytokines upregulated collagen, TF, α-SMA, MMP-1, and wound healing rate and downregulated fibronectin and MMP-9. IL-17 and IL-23 upregulated fibronectin, and IL-22 downregulated TF. IL-17 and IL-22 decreased wound healing rate. Similar to TGF-β, IL-23 upregulated MMP-1, tissue inhibitor of metalloproteinases–1, collagen expression, and wound healing rates. Conclusions: Our results suggest that cSEMFs have a central role in inflammation and fibrosis, as they express a great variety of Th-related cytokine receptors, making them responsive to pro-inflammatory cytokines, abundant in the inflamed mucosa of CD patients.